Spolno nadlegovanje na območjih nočnega življenja v Pomurju - Bulovec, Tinkara (Anali PAZU HD, 2021)
Nightlife areas, including bars, clubs, and restaurants, provide opportunities for various forms of physical, psychological, or sexual violence and/or abuse, which are in these places often conditioned by alcohol abuse by both the perpetrator and the victim. This paper aims to present the manifestation of sexual harassment, emphasizing the occurrence of such issues in Pomurje nightlife areas. Sexual harassment occurs in various forms and includes verbal and nonverbal behaviours that are offensive, hostile, or degrading to the victim and are related to the victim%s gender, gender expression, or sexual orientation. Acts of sexual harassment include unwanted sexual attention, making comments, displaying or distributing sexually related content, unwanted touching, and repeated requests for sexual intercourse, which in extreme cases may result in attempted or committed rape. Existing data on the number of sexual harassment incidents represent only the tip of the iceberg, as victims most often do not report incidents of sexual harassment to the competent authorities. Mentioned leads to the emergence of a dark field of unreported crime. The latter is also affected by the outbreak of the COVID-19 pandemic and the accompanying security measures, which have caused young people%s parties movement from public events and bars to private spaces. (Young) Pomurje residents participate in various events during the nightlife, both in their home region and elsewhere in Slovenia. Consequently, they can (possibly) become victims of different forms of (sexual) harassment, which the authors discuss in the article.
Keywords: nightlife; nočno življenje; Pomurje; sexual harassment; Slovenia; Slovenija; spolno nadlegovanje